METAFUNCTION ANALYSIS IN NEWS ITEM: A SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Nurfithri, M.Hum (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
This research is aimed at identifying the generic structure in the news item and lexico grammatical drawn in the news item. The analysis is intended to reveal meaning contained in the text by employing systemic functional linguistics approach. This study was conducted by qualitative descriptive method to analyze and describe the data. The data of this research an article about the governor of Yogyakarta, Sri Sultan HB X who made the decision to appoint his daughter as his successor. This article was taken on 10 May 2015 from http://www.thejakartapost.com/news/2015/05/08/sultan-half-brothers-discusssuccession.html. The result of the analysis showed that: the generic structure of news item can be newsworthy event, background event and comment. The lexico grammatical of this genre are mostly used verbal, material and attributive process, mostly used circumstantial of time and place, used past tense and used nominal group (six half brothers, Suryodiningrat and Sri Sultan HB X) as the main subject.